2005
DOI: 10.1080/03009740510017959
|View full text |Cite
|
Sign up to set email alerts
|

Reproduction and gynaecological manifestations in women with primary Sjögren's syndrome: a case‐control study

Abstract: Patients with pSS reported more gynaecological problems than controls, including vaginal sicca symptoms, endometriosis, several episodes of amenorrhoea, and menorrhagia/metrorrhagia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(26 citation statements)
references
References 12 publications
1
24
0
1
Order By: Relevance
“…26 Second, female patients with sicca syndrome might suffer from local irritation of the urinary bladder due to vaginal sicca. 6,27 Finally, Tishler et al 10 reported that patients with RA and secondary SS had a higher prevalence of urinary tract infections, which could also be a contributing factor to overactive bladder.…”
Section: Discussionmentioning
confidence: 98%
“…26 Second, female patients with sicca syndrome might suffer from local irritation of the urinary bladder due to vaginal sicca. 6,27 Finally, Tishler et al 10 reported that patients with RA and secondary SS had a higher prevalence of urinary tract infections, which could also be a contributing factor to overactive bladder.…”
Section: Discussionmentioning
confidence: 98%
“…Hyperactive bladder and increased fluid intake related with chronic dry mouth may be the underlying causes (19). Local irritation of the bladder that is attributed to vaginal dryness in the patients with RA and SS could also contribute to the disease process (5,20). Nephritis and/or nephropathy-induced conditions, including urinary tract infections, hematuria, and pyuria, can also exacerbate LUTS (19).…”
Section: Discussionmentioning
confidence: 99%
“…AUASI questionnaire includes seven questions to query the presence of a possible irritative (frequency, urgency, and nocturia) and obstructive (incomplete emptying, decrease in flow rate, and straining) urinary symptoms. A scoring system was utilized to classify the degree of the symptoms as mild (0-7), moderate (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19), or severe (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35). The final item of the AUASI form investigates the impact of urinary symptoms on QoL, and this entity is scored between 0 and 6 (10).…”
Section: Methodsmentioning
confidence: 99%
“…Patients with pSS reported more gynecological problems than controls, including vaginal sicca symptoms, endometriosis, several episodes of amenorrhoea, and menorrhagia/metrorrhagia [55]. Vasculitis, as demonstrated by the presence of perivascular infiltrations in vaginal tissues from these patients, rather than glandular dysfunction, seems to account for the vaginal dryness, as vaginal lubrication is mainly related to transudate from vaginal walls [54].…”
Section: Obstetrical and Gynecological Complicationsmentioning
confidence: 98%